Replace, absorb, serve: Data scientists talk about their aspired jurisdiction - Avnoon, Netta (Current Sociology, 2024)
How do data scientists frame their relations with domain experts? This study focuses on data scientists' aspired professional jurisdiction and their multiple narratives regarding data science's relations to other fields of expertise. Based on the analysis of 60 open-ended, in-depth interviews with data scientists, data science professors, and managers in Israel, the findings show that data scientists institutionalize three narratives regarding their relations with domain experts: (a) replace experts, (b) absorb experts' knowledge, and (c) provide a service to experts. These three narratives construct data scientists' expertise as universal and omnivorous; namely, they are relevant to many domains and allow data scientists to be flexible in their claim for authority.
Keywords: Algorithms; Data Science; Expertise; Interprofessional Relations; Professional Jurisdiction; Artificial Intelligence